Pengaruh Budaya Korporat terhadap Produktivitas Kerja Karyawan pada PT. Bank Mandiri (Persero) Tbk Cabang Ambon - Olivia Laura Sahertian (STIE Widya Manggala, 2012)
Corporate culture is dominat values which spread within a company and act as working philosophy to manage employee in order to increase employee productivity. Bank Mandiri has developed appropriate culture which in line with vision and mission. This serve is as the role model and guidance to make a desicion. Corporate culture covers trust, integrity, professionalism, customer focus and exellence. The purpose ofthis research was to know the influence of corporate culture to employee productivity at PT. Bank Mandiri (Persero) Tbk Cabang Ambon. This research was conducted at PT. Bank Mandiri with 98 respondents. The data was collected by questionnaire, interview and documentation. It used regression to analyze. The result showed that corporate culture, consist of trust, integrity, professionalism, customer focus and exellence had positive influence simultaneously to employee productivity. Partiality, trust, integrity, professionalism, customer focus and exellence had positive influence to employee productivity. Integrity was a dominant variable which had positive influence to employee productivity.